Effect of rapamycin on bone mass and strength in the α2(I)‐G610C mouse model of osteogenesis imperfecta. Issue 3 (30th December 2018) - Bateman, John F.; Sampurno, Lisa; Maurizi, Antonio; Lamandé, Shireen R.; Sims, Natalie A.; Cheng, Tegan L.; Schindeler, Aaron; Little, David G.
Abstract: Osteogenesis imperfecta (OI) is commonly caused by heterozygous type I collagen structural mutations that disturb triple helix folding and integrity. This mutant‐containing misfolded collagen accumulates in the endoplasmic reticulum (ER) and induces a form of ER stress associated with negative effects on osteoblast differentiation and maturation. Therapeutic induction of autophagy to degrade the mutant collagens could therefore be useful in ameliorating the ER stress and deleterious downstream consequences. To test this, we treated a mouse model of mild to moderate OI (α2(I) G610C) with dietary rapamycin from 3 to 8 weeks of age and effects on bone mass and mechanical properties were determined. OI bone mass and mechanics were, as previously reported, compromised compared to WT. While rapamycin treatment improved the trabecular parameters of WT and OI bones, the biomechanical deficits of OI bones were not rescued. Importantly, we show that rapamycin treatment suppressed the longitudinal and transverse growth of OI, but not WT, long bones. Our work demonstrates that dietary rapamycin offers no clinical benefit in this OI model and furthermore, the impact of rapamycin on OI bone growth could exacerbate the clinical consequences during periods of active bone growth in patients with OI caused by collagen misfolding mutations.